The mediation of work environment on employee performance through organizational culture and work discipline - Imam Riyadi; Yadi Supriadi; Juwizat Juwizat; Wahyudi Wahyudi; Ahmad Solihin (Institute of Computer Science (IOCS), 2026)
This study examined how organizational culture and work discipline affect employee performance, with the work environment serving as a mediating factor at PT Telkom Indonesia's Banten Region, Ciruas Office. A quantitative research method using an ex post facto design was used to investigate the connections between the variables. The study included 100 employees who were chosen through a saturated sampling method, which ensured that every individual in the population took part as a respondent. Data were gathered using structured questionnaires, which were evaluated on a 10-point Likert scale, and then analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results showed that both the organization's culture and the level of work discipline had a positive and statistically significant impact on how well employees performed. In addition, these variables had a significant impact on the quality of the work environment. Among all the variables that were studied, the work environment had the most significant direct effect on how well employees performed. In addition, the work environment was identified as playing a major role in influencing how organizational culture, work discipline, and employee performance are connected. These results suggest that how well an employee performs is not only influenced by factors within the organization itself but is also affected by the overall working environment in a more indirect way. Therefore, organizations need to pay attention to building a strong organizational culture, improving employee behavior, and establishing a workplace that supports employees, in order to boost their performance and better accomplish the goals of the organization.